2019
DOI: 10.1039/c9tb00367c
|View full text |Cite
|
Sign up to set email alerts
|

Alignment and bioactive molecule enrichment of bio-composite scaffolds towards peripheral nerve tissue engineering

Abstract: Providing topographical cues along with chemical and biological factors is essential for biomimetic scaffolds applied in nerve tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…To overcome these limitations, this synthetic polymer is mixed with natural bio-active agents such as proteins, growth factors, etc. A collagen (COL) compound was chosen for the fabrication of our conduit after a prior optimization study, which revealed superior proneurogenic feature of P(LLA-CL) with collagen compared to pristine synthetic polymer [ 14 ]. Polyanilin (PANI) was added because of its electroconductive features, which promote neuroregeneration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, this synthetic polymer is mixed with natural bio-active agents such as proteins, growth factors, etc. A collagen (COL) compound was chosen for the fabrication of our conduit after a prior optimization study, which revealed superior proneurogenic feature of P(LLA-CL) with collagen compared to pristine synthetic polymer [ 14 ]. Polyanilin (PANI) was added because of its electroconductive features, which promote neuroregeneration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that electrospun nanofibers can reproduce the tissue ECM and offer a sufficient biomimetic environment for cell adhesion, growth, and differentiation, favoring a better tissue regeneration. [ 158,162–164 ] Electrospinning parameters such as polymer concentration to be dissolved in the solvent solution, flow rate, voltage, working distance or ambience conditions can be manipulated to control fiber diameter, porosity, and mechanical strength of the electrospun scaffold. It has been demonstrated that nanofibrous constructs have greater mechanical properties than bulk polymer material and enhance cell proliferation, metabolic activity, and matrix expression.…”
Section: Fiber‐based Engineered Scaffolds For Tendons and Ligamentsmentioning
confidence: 99%
“…Such SGN regrowth will also be necessary to reinnervate regenerated hair cells, as that becomes feasible. Strategies to direct neurite guidance have commonly relied on the use of patterned bioactive molecules (Branch et al, 1998;Branch, Wheeler et al, 2001;Gustavsson et al, 2007;Kijenska-Gawronska et al, 2019;Millet et al;Tuft et al, 2014). Using techniques such as microcontact printing, surface modification for selective adsorption, and microfluidics, patterns of peptides that guide neurite growth have been created and used as platforms for directed neurite regeneration (Belisle et al, 2008;Fricke et al, 2011;Honegger et al, 2016;Joo et al, 2015;Klein et al;Wittig et al, 2005).…”
Section: Introductionmentioning
confidence: 99%